Deciphering the role of hole transport layer HOMO level on the open circuit voltage of perovskite Solar cells - Jiang,Z; Du,T; Lin,C; Macdonald,TJ; Chen,J; Chin,Y; Xu,W; Ding,B; Kim,J; Durrant,JR; Heeney,M; McLachlan,MA (Advanced Materials Interfaces, 2023)
With the rapid development of perovskite solar cells, reducing losses in open-circuit voltage (Voc) is a key issue in efforts to further improve device performance. Here it is focused on investigating the correlation between the highest occupied molecular orbital (HOMO) of device hole transport layers (HTLs) and device Voc. To achieve this, structurally similar HTL materials with comparable optical band gaps and doping levels, but distinctly different HOMO levels are employed. Using light-intensity dependent Voc and photoluminescence measurements significant differences in the behavior of devices employing the two HTLs are highlighted. Light-induced increase of quasi-Fermi level splitting (ΔEF) in the perovskite layer results in interfacial quasi-Fermi level bending required to align with the HOMO level of the HTL, resulting in the Voc measured at the contacts being smaller than the ΔEF in the perovskite. It is concluded that minimizing the energetic offset between HTLs and the perovskite active layer is of great importance to reduce non-radiative recombination losses in perovskite solar cells with high Voc values that approach the radiative limit.